ANALISIS INDEKS KEPUASAN MASYARAKAT DALAM PENGELOLAAN DAN PERTANGGUNGJAWABAN ALOKASI DANA DESA DI KABUPATEN KONAWE SELATAN - Ilham, Muhammad; Syahrir, Andi; Lestari, Dian Trianita; Sultrayansyah, Sultrayansyah (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
This research aims to analyze the community satisfaction index in village financial management and accountability, including Village Fund Allocation in South Konawe Regency. The focus of this research is on village financial management and accountability as well as measuring the community satisfaction index with this management and accountability. The research method used is descriptive with a qualitative approach but still has quantitative data for the focus of the second research. The selection of respondents was carried out using the Cluster sampling method which resulted in five sample sub-districts, namely Andoolo, Ranomeeto, North Moramo, Tinanggea and Laonti sub-districts. Meanwhile, data collection techniques are divided into three types, namely interviews, documentation and questionnaires. The types of data in this research are divided into two types, namely qualitative and quantitative. Qualitative data was analyzed through three stages, namely data reduction, data presentation and drawing conclusions. Meanwhile, quantitative data was analyzed using the weighted average value of 9 elements in the use of village funds. The research results show that village financial management and accountability, which consists of the planning, implementation, administration, reporting and accountability stages in South Konawe Regency, has generally run well and follows statutory regulations. However, the transparency aspect still needs to be improved, especially in terms of information on the use of village income and expenditure budgets that can be accessed by the entire community. On the other hand, the results of measuring the community satisfaction index in village financial management and accountability in South Konawe Regency generally show a perception of satisfaction with a good rating and the quality of community satisfaction is rated B with a number of 86.39. It is hoped that this value can increase in the future by maximizing the role of each party directly involved in the management and accountability of village finances, such as the Village Head, Village Treasurer, Village Consultative Body, South Konawe Regency Community and Village Empowerment Service and South Konawe Regency Regional Inspectorate.